Shifting of Attention in the Interpretation of Ibn Abi al-Rabi’ al-Ishbili - Hussin, Mohamad; Al Futaiman, Sheimah Mohammad; Pa, Mat Taib (Al-Ḍād Journal, 2025)
The research aims to elucidate the technique of Iltifāt (shifting of attention) in the Holy Quran. It also seeks to uncover the scope and benefits of Iltifāt, highlighting its conditions, categories, and rhetorical purposes. The researcher adopted both the descriptive and inductive methodologies in this study. The research concluded with several key findings: Iltifāt has general benefits such as the artful transition from one style to another to engage the listener and protect them from monotony and boredom by avoiding a single, unchanging pattern. The conditions for Iltifāt include the requirement that the pronoun in the shifted context refers to the same subject as the original context, that the pronoun appears in two sentences, and that the addressee remains the same in both contexts. The categories of Iltifāt involve shifting from speaking in the first person to addressing in the second person, from the first person to the third person, and from the second person to the third person. Among the characteristics of Ibn Abi Rabi' Al-Ishbili's interpretation are the diversity of his sources, including books like Al-Kashshāf by Al-Zamakhshari and Al-Muwattā’ by Imam Malik. He focused on rhetorical aspects in his interpretation, linking semantics with syntax and various readings, and connecting the meanings of words with their syntax and different readings. Additionally, he avoided referencing Israeli traditions, relying mainly on Quranic texts and prophetic traditions. His interpretation extensively used rational analysis and frequently cited poetic evidence to support his interpretations. Keywords: Iltifāt, al-Quran al-Karim, Rhetorical Styles, Tafsīr of al-Ishbīli.